Disain Kompor Listrik Dengan Menggunakan Pembangkit Listrik Tenaga Surya Untuk Kebutuhan Listrik Rumah Tangga - Novi Gusti Pahiyanti; Sigit Sukmajati; Indrianto Indrianto (Sutet, 2021)
Savings in using electric fuel in the use of fossil fuel electricity must be reduced. This research was conducted as an effort to save the use of electricity by using solar power plants as the main source, with the making of this research it is hoped that it can be used for electricity consumption at a more economical cost and the use of electric stoves can be used in daily life. The selection of materials and this research can be seen from the existing literature and field studies. Solar power plants in this study use some equipment such as solar panels that by utilizing solar energy will be a source of initial voltage, a regulator control battery as a regulator of electric power charging to the battery (battery), battery (battery) as a storage of electrical power, and an inverter for convert the dc to ac voltage from the battery (battery). The equipment is the main equipment used to turn on the electric stove which is the main burden in this application. This research is expected to be a reference for the use of solar energy for electric stoves in an effort to save electricity. This equipment also refers to the amount of power used on an electric stove of 300 W, with an observation time of 7 hours a day, so that it will produce a current that flows at 6.8 A, and a voltage of 17.3 Volts which occurs at 11.00 WIB